Dalla condizione terrestre all’ambiente planetario nei Canti di Giacomo Leopardi - Loba, Mirosław (Studia Romanica Posnaniensia, 2022)
This article examines the representation of the environment in the Canti by Giacomo Leopardi. The author seeks to show the Leopardian environment as a place where history, nature and the cosmos intersect. The immensity and simultaneity of these three elements determines the way the lyric subject inhabits the world. Leopardi’s poetic focus is on his painful experience of the environment, which remains an indifferent and destructive agent. The poet deconstructs classical and romantic models of nature and culture by appealing to the aesthetics of the sublime, which unlike Kant is not the means of understanding but the way to experience the planetary character of existence.